Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Siswa Pada Pembelajaran Pkn Kelas V Sdn 15 Ampang Gadang Kecamatan Ampek Angkek Kabupaten Agam - Arrahim, Raffi; Arlis, syamsu; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
The aim of this study is to determine the effect of the problem based learning (PBL) model on the learning result PKn in fifth grade of SDN 15 Ampang Gadang Kabupaten Agam in first semester in 2018/2019. The type of this research is quasi experimental research. The sample of this research is fifth grade students of SDN 15 Ampang Gadang. Based on the results of the analysis by using t-test, researcher find that the result of t-count is 2,51 and t-table at significant level α =0.05 is 2.02, so t-count>t-table. This shows there is a significant effect in applying problem based learning (PBL) model on the learning result PKn in fifth grade of SDn 15 Ampang Gadang Kecamatan Ampek Angkek Kabupaten Agam.